KEY COMPETENCIES OF PUPILS IN REFLECTION OF TECHNICAL EDUCATION - VALENTOVA, Monika; BRECKA, Peter (Trends in education, 2015)
This paper deals with the development of pupils key competencies in the subject technology through teaching modules designed by us with the use of interactive whiteboard. On specific thematic unit we refer possibilities of development for selected key competences. These are compatible with the systems of key competences in OECD countries and the EU
Keywords: key competencies; technology; interactive whiteboard.